Analisis Daur Hidup Proses Produksi Beton RCC dengan Substitusi Parsial Terak Nikel (Studi Kasus Laboratorium Struktur dan Material, Fakultas Teknik, Universitas Indonesia) - Pratiwi, Siva Yuniar; Rahmatika, Iftita; Viandila Dahlan, Astryd; Sjah, Jessica; Handika, Nuraziz (Syntax Corporation, 2025)
Concrete is the most widely used construction material in infrastructure development. The main components of concrete consist of coarse aggregate (gravel/split stone), fine aggregate (sand), cement and water. The massive use of natural aggregates raises concerns about their future availability. Nickel slag, which has similar chemical characteristics to natural aggregates, has the potential to be a sustainable substitution material. This study aims to analyze the environmental impact of the Roller Compacted Concrete (RCC) concrete production process with 50% nickel slag substitution for natural aggregates using the Life Cycle Assessment (LCA) approach. The approach used is gate to gate with units per 1 m3 of concrete and analyzed using OpenLCA software and the ReCiPe2016 method. The results of the analysis showed that the RCC concrete compaction stage produced household gas emissions of 1,030.42 kg CO2 eq for Scenario 1 and 1,108.27 kg CO2 eq and for Scenario 2. At the transportation stage, it is known that the largest emission results come from the delivery process of PT. Y to the Laboratory as far as 28 km, which is 1,521.18 kg CO2 eq. Based on these results, it is recommended that the selection of material providers consider comparable mileage to reduce the environmental impact of the transportation process.